Olive polyphenols: new promising agents to combat aging-associated neurodegeneration. (3rd April 2017) - Casamenti, Fiorella; Stefani, Massimo
ABSTRACT: Introduction: Clinical trials and population studies indicate the healthy virtues of the Mediterranean diet and its main lipid component, extra-virgin olive oil (EVOO). Olive leaves and EVOO contain many phenolics effective against several aging and lifestyle-related diseases, including neurodegeneration, both in animal models and in humans. Recent research has shown that such protection stems from several effects, including (i.) the interference with the aggregation of peptides/proteins found in amyloid diseases, particularly in Alzheimer's and Parkinson's diseases; (ii.) the protection of cells and tissues against aging-associated functional derangement (ion/redox homeostasis, aberrant cell signaling, etc.); (iii.) the transcriptional modulation through epigenetic modifications. Area covered: We used MEDLINE for literature reference; we also searched ClinicalTrials.gov to select clinical trials with olive oil and/or its polyphenols that suggested their potential particularly for what neuroprotective therapy is concerned. Expert commentary: We focus the relation between diet components, particularly olive polyphenols, and protection against the occurrence of the most widespread neurodegenerative conditions associated with aging. The need of more clinical studies in humans to confirm the results obtained in animal and cell models to definitely support the utility of these molecules to combat or to delay the symptoms associated to aging-associated neurodegeneration is also stressed.